PENERAPAN MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN PEMAHAMAN HUKUM BACAAN QOLQOLAH DAN HASIL BELAJAR SISWA KELAS V SD 027 BALIKPAPAN - Sufyansyah Sufyansyah (Universitas Islam Balitar, 2015)
This study focuses on the implementation of cooperativelearning models to increase achievement on rules of qolqolah inreading the holly Alquran. The subject of this study is the fifthgrade students of SDN 027 Balikpapan. This study usesclassroom action research design with two cycles. The resultsof classroom participation indicate that an increase is achievedfrom 40% in the cycle I into 72% in the cycle II. The masterylearning also increases from 64% to 100% respectively in cycle Iand cycle II. This study concludes that teaching reading rules ofqolqolah in reading Alquran using cooperative learningincreases students learning activities and readingcomprehension.